2006
DOI: 10.1177/0146167206288599
|View full text |Cite
|
Sign up to set email alerts
|

Personality Plasticity After Age 30

Abstract: Rank-order consistency of personality traits increases from childhood to age 30. After that, different summaries of the literature predict a plateau at age 30, or at age 50, or a curvilinear peak in consistency at age 50. These predictions were evaluated at group and individual levels using longitudinal data from the Guilford-Zimmerman Temperament Survey and the Revised NEO Personality Inventory over periods of up to 42 years. Consistency declined toward a non-zero asymptote with increasing time-interval. Alth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
278
4
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 393 publications
(309 citation statements)
references
References 37 publications
(79 reference statements)
22
278
4
2
Order By: Relevance
“…In order to do so, we used longitudinal data from a large national probability sample of adults in the core midlife, and investigated personality trait development from three different perspectives. First, replicating prior findings (Roberts and DelVecchio 2000;Terracciano et al 2006), we found medium to high rankorder stability of the Big Five personality traits over 10 years with an average stability coefficient of .67. Although rank-order stability of personality traits was relatively high, this does not imply that there are no reliable individual differences in personality change.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In order to do so, we used longitudinal data from a large national probability sample of adults in the core midlife, and investigated personality trait development from three different perspectives. First, replicating prior findings (Roberts and DelVecchio 2000;Terracciano et al 2006), we found medium to high rankorder stability of the Big Five personality traits over 10 years with an average stability coefficient of .67. Although rank-order stability of personality traits was relatively high, this does not imply that there are no reliable individual differences in personality change.…”
Section: Discussionsupporting
confidence: 84%
“…For example, research has shown that personality traits demonstrate relatively high structural stability, i.e., constant correlations among personality factors within measurement occasions, implying that the positioning of traits relative to each other remains stable and are unaffected by age and aging (Allemand et al 2008(Allemand et al , 2007. Moreover, research demonstrated high levels of rank-order stability, i.e., high correlations within personality factors across measurement occasions, implying that individuals keep their ranking in a reference group over time (Roberts and DelVecchio 2000;Terracciano et al 2006). At the same time, previous research demonstrated systematic age differences and age-related changes in the mean-levels of personality traits in adulthood (Donnellan and Lucas 2008;Jackson et al 2009;.…”
Section: Personality Trait Development In Midlifementioning
confidence: 92%
“…Importantly, although we found familiar patterns of age differences in cognitive functioning (Salthouse, 2006), personality traits (Roberts et al, 2006;Terracciano, Costa, & McCrae, 2006), and subjective physical health (CDC, 2007), none of these showed any association with discounting rates. Moreover, in-depth analyses of switch points and discounting functions showed no indication that the consistency of response patterns differed by age.…”
Section: Discussionmentioning
confidence: 77%
“…First, personality in adulthood is more stable over time than personality in adolescence [Roberts & DelVecchio, 2000;Terracciano et al, 2006]. As such, reliabilities of ratings might differ between two settings because of age differences of the subjects in these settings.…”
Section: Discussionmentioning
confidence: 99%